Kalaripayatuu - Lal, Vinay (1998)
[Dt.:] Vinay Lal ist Associate Professor am Historischen Institut der University of California und Autor zahlreicher Bücher über indische Geschichte und Kultur. Auf seiner Homepage "Manas" finden sich einführende Texte und weiterführende Verlinkungen zu einem breiten Spektrum kultureller Handlungspraxen des indischen Subkontinents. Unter der Rubrik "Tanz" führt er in die in Kerala beheimatete Tradition des Kalaripayatuu ein, ein Kampfsport, dessen Wurzeln bis ins 1. Jahrhundert v. Chr. zurückreichen sollen. - [Engl.:] Vinay Lal is Associate Professor at the UCLA History Faculty and author of many books on Indian culture and history. On his web site "Manas" he offers introducing texts and continuative links that pick out the wide range of cultural agencies as a central theme. In the issue "Dances" he sketches a martial arts tradition from the coastal state of Kerala, Kalaripayatuu - "the arts of the gymnasium" - that is believed to have a history extending back to the first century AD.